Job Satisfaction as a Mediator in Improving the Hospitality Industry Employees’ Performance Through Knowledge Management Practices - Goyal, Arpita; Mansi,; Pandey, Shubham (Prabandhan: Indian Journal of Management, 2026)
Purpose : The purpose of this study was to investigate the relationship between knowledge management (KM) and organizational performance (OP) through employee job satisfaction (JS). If knowledge management has an impact on JS and subsequently OP, then organizations can develop KM systems that will allow them to develop strategies to improve their overall performance. Methods : A structural equation modeling (SEM) methodology was employed using a sample of 190 staff from the hospitality industry in Madhya Pradesh, India, to investigate the relationship between KM and OP with a focus on JS as a mediator. Results and Findings : The results and findings provided strong evidence for the positive impact of KM on OP, as well as JS, as having a substantial role in mediating the relationship between KM and OP. Practical Implications : The results bring out the meaningfulness of designing and executing KM practices to strengthen job fulfilment and hence organizational productivity. As such, organizations providing hospitality services should recognize the role of KM and utilize it as a means to buildup organizational outcomes; furthermore, by focusing more on improving JS as a result/outcome of KM, organizations might be able to additionally strengthen the positive impact of KM on OP/productivity. Originality : The KM practices used in the study are regarded as novel compared to those referenced in previous literature. The distinctiveness of this study thus adds value to the existing literature in providing new perspectives into how organizations can improve their performance through improved KM practices.